Is calprotectin a reliable marker in surgical ICU settings? A clinical evaluation of its role in sepsis and mortality prediction - Aladağ, Ebru; Zora, Muhammed Emin; Gültekin, Yücel; Mızrak, Soycan (Frontiers in Medicine, 2025)
BackgroundCalprotectin, a neutrophil-derived protein, has emerged as a potential biomarker for inflammation and infection. This study evaluated the utility of serum calprotectin levels in diagnosing sepsis and predicting mortality in surgical intensive care unit (ICU) patients.MethodsThis prospective observational study included 124 patients admitted to the surgical ICU at Uşak Training and Research Hospital between 2022 and 2024. Data on demographics, serum calprotectin, CRP, PCT, lactate levels, and clinical scores (SOFA, APACHE II) were collected. ROC analysis was used for predictive accuracy; Spearman and Pearson correlation coefficients assessed associations.ResultsNo significant associations were found between serum calprotectin and SOFA/APACHE II scores, CRP, or lactate. However, calprotectin correlated positively with PCT in sepsis (r = 0.428, p = 0.002) negatively in postoperative subgroups (r = −0.48, p < 0.001). Calprotectin showed poor prognostic accuracy (AUC = 0.472). Mortality was significantly associated with high CRP and severity scores, but not with calprotectin levels.ConclusionCalprotectin alone lacks sufficient diagnostic or prognostic power for sepsis in surgical ICU patients. It may serve as a complementary marker alongside PCT in specific subgroups.